NEED ANALYSIS ON ENGLISH TEACHING MATERIALS FOR ICT STUDENTS - Sri Diana; Musdalifah Mansur (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
The research aims to find out the English Materials need of the students of Genetic Computer School Singapore in Learning English. The quantitative and qualitative method were conducted in this research to provide the description of the students’ needs. In collecting the data, the researcher applied interview for lecturers and questionnaire for the students as the instrument of the research. There were two lecturers and thirty of second-semester students in the 2017-2018 academic year as participants in this research by conducting purposive sampling.The result of this research revealed that students of Information, Communication and Technology (ICT) mostly needed two skills in learning English. First, speaking skill that is to communicate in English and to present their final project exam. Second, writing skill is used to do their assignment and final report in English. Language element which most important and needed by the students is vocabulary, then followed by grammar. The interview result showed that in teaching English the lecturers do not have permanent syllabuses for four semesters and the existing materials are design based on lecturers perception, it is not based on students needs. The information of this research as the recommendation for the institution that might be used as guidance to design the English syllabuses.